KETERBATASAN SARANA PENYIMPANAN ARSIP FISIK DAN IMPLIKASINYA TERHADAP MANAJEMEN ARSIP - Nayla Eka Syamsiyah; Riskika Velania Istiqomah; Putri Dewi Stefany; Fauzia Rosalia Trisnia; Lilik Huriyah (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2026)
This study examines the limitations of physical archive storage facilities and their implications for archives management in various institutions. Archives play a crucial role as a source of information, evidence, and organizational memory, supporting smooth administration. However, in practice, many institutions still face limitations in space and storage facilities, as well as suboptimal archives management. This study employed a qualitative method with a literature study approach through analysis of various relevant literature sources. The results indicate that limited storage facilities lead to archive accumulation, disorganization in organization, difficulty in document retrieval, and an increased risk of damage and loss. The main contributing factors include budget constraints, low priority of archives management, increasing archive volume, and suboptimal digitization. The implications of these conditions result in decreased work effectiveness, service quality, and organizational accountability. Therefore, improvements are needed through the provision of adequate facilities and infrastructure, the implementation of a systematic classification system, increased human resource competency, and the optimization of digital technology in archives management